MENINGKATKAN KETERAMPILAN MOTORIK HALUS ANAK USIA 4-5 TAHUN MELALUI KEGIATAN MELUKIS DENGAN PASIR - Tika Mardiana; Ratih Kusumawardani; Rr Dina Kusuma Wardhani (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2017)
This study aims to (1) know the application of painting activities with sand can improve the fine motor skills aged 4-5 years in TK Kemala Bhayangkari 01 serang, (2) and know the activity of painting with sand can improve the fine motor skills of children aged 4-5 years in kindergarten Kemala Bhayangkari 01 Serang. The research type is action research using model of Kemmis and Mc Taggart. Research subjects were 17 children aged 4-5 years in TK Kemala Bhayangkari 01 Serang Banten. The object research is the fine motor skill of children. Methods of data collection is done through observation, interview and documentation. Data analysis technique is done qualitatively. The success indicator in this researxh is 60%. The results showed that the fine motor skills of child increased to 93% of the prestudy by 29% the result up in the first cycle of 56% and un the second cycle of the 93% of the results it can be concluded that the activity of painting with sand can improve fine motor skills ofchildren aged 4-5 years in TK Kemala Bhayangkari 01 Serang Banten.